Peningkatan Kesadaran Masyarakat Melalui Sosialisasi Mitigasi Bencana Abrasi Pantai (Studi Kasus di Negeri Lima) - Puturuhu, Ferad; Ruman, Rifyan; Hatuala, Siti Hana; Tomagola, Rabiah Tum (EMPOWERMENT: Journal of Community Practice, 2024)
Coastal erosion is one of the natural disasters that frequently occurs in coastal areas and can threaten the sustainability of ecosystems and the lives of local communities. Negeri Lima, as one of the coastal villages, faces a significant threat of coastal erosion. This research aims to increase the awareness of the Negeri Lima community regarding coastal erosion disaster mitigation through a socialization program implemented by KKN students. The method used in this research is a participatory approach involving local communities in various socialization activities. The results show that the disaster mitigation socialization successfully increased community knowledge and awareness about coastal erosion and its mitigation measures. Moreover, the active participation of the community in these activities also improved their preparedness in facing the threat of coastal erosion. These findings indicate that a structured socialization program involving community participation can be an effective strategy in enhancing coastal community resilience against coastal erosion disasters